Disorientasi Politik dan Peran Intermediary Kelas Menengah To Pulo: Politik Lokal di Kepulauan Selayar Pasca Orde Baru - Abu Bakar (Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
This paper discusses the emergence of social movements To Pulo with the issue of a new government and thedevelopment of the New Order. Today, the issue is increasingly disappearing in local political discourse inKepulauan Selayar. This paper will explore how these things to happen to focus on the political disorientationand why the role of intermediary actors To Pulo weakened middle class. To explain this case, the use of socialmovement theory perspective of social identity theory and case study research method. The purpose of thispaper to describe a social movement To Pulo by answering questions; how To Pulo social movements?; Whydid political disorientation inside could be happened?; Why did middle-class intermediary role ﬁ zzle?. The conclusion is the disorientation caused by the absence of a strong commitment. And the weak role of the intermediary is caused by internal conﬂ icts To Pulo.